2018
DOI: 10.1055/s-0038-1673360
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Surgery for Carpal Tunnel Syndrome: A New Interventional Procedure

Abstract: Carpal tunnel syndrome (CTS) may be treated surgically if medical treatment fails. The classical approach involves release of the flexor retinaculum by endoscopic or open surgery. Meta-analyses have shown that the risk of nerve injury may be higher with endoscopic treatment. The recent contribution of ultrasound to the diagnosis and therapeutic management of CTS opens new perspectives. Ultrasound-guided carpal tunnel release via a minimally invasive approach enables the whole operation to be performed as a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The metrics used to demonstrate nerve decompression were CSA of the median nerve and changes in nerve position, both measured at the level of the hamate. 21 Results of our MRI analysis agree with the findings of Petrover et al, 11 as both investigations reported a complete transection of the TCL in 100% of the cases, a significant increase in median nerve CSA, and a palmar shift of the median nerve. Our investigation expands this work by documenting increased carpal tunnel dimensions, reduced flattening ratios of the median nerve and carpal tunnel (ie, reduced flattening), and reduced median nerve T2 signal intensities.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The metrics used to demonstrate nerve decompression were CSA of the median nerve and changes in nerve position, both measured at the level of the hamate. 21 Results of our MRI analysis agree with the findings of Petrover et al, 11 as both investigations reported a complete transection of the TCL in 100% of the cases, a significant increase in median nerve CSA, and a palmar shift of the median nerve. Our investigation expands this work by documenting increased carpal tunnel dimensions, reduced flattening ratios of the median nerve and carpal tunnel (ie, reduced flattening), and reduced median nerve T2 signal intensities.…”
Section: Discussionsupporting
confidence: 90%
“…Multiple studies have reported statistically significant and clinically meaningful improvements in patient-reported outcomes following CTR-US. 3 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 Despite these encouraging clinical results, the morphological changes within the carpal tunnel following CTR-US have not been fully characterized. Previous research has used magnetic resonance imaging (MRI) to document morphological changes consistent with carpal tunnel decompression (eg, TCL transection, increased carpal tunnel dimensions, and reduced median nerve compression) following open and endoscopic carpal tunnel release (ECTR).…”
mentioning
confidence: 99%
“…Overall, revision due to incomplete release after CTR-US is uncommon, commensurate with MRI studies documenting successful decompression after CTR-US. 44 , 45 , 46 , 47 …”
Section: Discussionmentioning
confidence: 99%
“…Petrover et al . demonstrated the safety and efficacy of minimally invasive HRUS-guided CTR ( 16 , 17 ) . A modified HRUS-guided CTR was also described by Loizides et al .…”
Section: Introductionmentioning
confidence: 98%
“…Beside open carpal tunnel release (CTR) and endoscopic procedures, minimally invasive procedures in various anatomical regions including the tarsal and carpal tunnel have attracted attention, as they are associated with little tissue trauma and are less invasive, thus producing fewer side-effects (7)(8)(9)(10)(11)(12)(13)(14)(15) . Petrover et al demonstrated the safety and efficacy of minimally invasive HRUS-guided CTR (16,17) . A modified HRUS-guided CTR was also described by Loi-zides et al using an additional blunt button tip cannula with several advantages: it allows for stump splinting of the carpal tunnel (CT), serves as a track for the subsequent insertion of the hook knife, and serves as a protection device between the median nerve (MN) and the hook knife.…”
Section: Introductionmentioning
confidence: 99%